2007
DOI: 10.21608/jvmr.2007.77888
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Babesia ovis in small ruminants in Siwa Oasis, Egypt

Abstract: A total of 240 blood samples were collected from 108 sheep and 132 goats for preparation of blood smears and for separation of serum samples and tested against B. ovis by using IFAT. B. ovis was detected in 55 (50.92%) and 59 (44.69%) blood smears examined in sheep and goats, respectively. The overall prevalence of B. ovis infection was 71.3% in sheep and 68.2% in goat using IFAT. The seasonal prevalence of B.ovis peaked in both spring and summer as revealed by blood smear examination and IFAT. A total of 143 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…of our study revealed that maximal infection rate was recorded during Summer months followed by Spring. These results agreed with that obtained by Gattas (1990) and Garcia et al (2006) in large animals Ramadan and El Akabawy (2000) and Hosein et al (2007) Fakhar et al (2012 Reda (2001), Ali (2005 and Guerrero et al (2007).…”
Section: Resultssupporting
confidence: 91%
“…of our study revealed that maximal infection rate was recorded during Summer months followed by Spring. These results agreed with that obtained by Gattas (1990) and Garcia et al (2006) in large animals Ramadan and El Akabawy (2000) and Hosein et al (2007) Fakhar et al (2012 Reda (2001), Ali (2005 and Guerrero et al (2007).…”
Section: Resultssupporting
confidence: 91%
“…During current survey PCR detected 69.8% prevalence which was higher so far within and outside Pakistan. The results of higher prevalence are in agreement with findings from Egypt [20], Iran [21,22] and Iraq [23] where up to 57% prevalence of Babesia in sheep has been reported. But contrary to present study, lower prevalence as low as just 5% was studied in Iran [21,24,25], Tunisia [26] and Turkey [27].…”
Section: Introductionsupporting
confidence: 91%
“…of studies carried out in Species molecularly confirmed by more than one study Ticks Animals Humans Babesia sp . * [ 32 , 33 , 45 , 98 ] ¶ [ 49 ] * [ 29 , 30 , [41] , [42] , [43] , [44] , 46 , 47 , [50] , [51] , [52] , [53] , 31 , [54] , [55] , [56] , 62 , 72 , [33] , [34] , [35] , [36] , [37] , 39 , 40 ] # [ 38 , 48 ] ¶ [ 49 ] ⁑ [ 61 ] # [ 57 , 58 , 60 ] ¶ [ 59 ] Babesia bigemina, Babesia bovis, Babesia caballi, Babesia canis vogeli, Babesia occultans Hepatozoon sp. * [ 62 ] ¶ [ 63 , 64 ] Theileria sp .…”
Section: Resultsmentioning
confidence: 99%